Transcriptome analysis reveals the molecular mechanism of Yiqi Rougan decoction in reducing CCl4-induced liver fibrosis in rats - Yu Xiong; Jinyuan Hu; Chen Xuan; Jiayu Tian; Kaiyue Tan; Zhiwei Chen; Yan Luo; Xuqin Du; Junxiong Cheng; Lanyue Zhang; Wenfu Cao (BMC, 2021)
Abstract Background Liver fibrosis develops from various chronic liver diseases, and there is currently a lack of specific treatment strategies. Yiqi Rougan decoction (YQRG) is a traditional Chinese medicine that has shown durative effects in the treatment of liver fibrosis; however, the mechanism associated with YQRG-related improvements in liver fibrosis remains to be experimentally determined. This study evaluated the therapeutic effect of YQRG on carbon tetrachloride (CCl4)-induced liver fibrosis in rats and its molecular mechanism. Methods We used low-, medium-, and high-dose YQRG to treat CCl4-induced liver fibrosis in rats, followed by assessment of liver injury and fibrosis according to liver appearance, body weight, liver mass index, histopathologic examination, and serum testing. Additionally, we performed transcriptome analysis using RNA-sequencing (RNA-seq) technology, including cluster, Gene Ontology (GO), and pathway analyses, to identify differentially expressed genes (DEGs), and protein and gene expression were detected by immunofluorescence (IFC), western blot and real-time quantitative PCR. Results The results showed that YQRG effectively alleviated CCl4-induced liver injury and fibrosis in rats, including observations of improved liver function, decreased activity of hepatic stellate cells (HSCs), and decreased extracellular matrix (ECM) deposition. Moreover, we identified downregulated and upregulated DEGs in the model group relative to the control and YQRG-treated groups, with GO analysis revealing their enrichment in biological processes, such as endoplasmic reticulum stress (ERS), apoptosis, and autophagy. Furthermore, pathway analysis showed that YQRG treatment downregulated the mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase/Akt (PI3K/AKT) signalling pathways and upregulated other signalling pathways, including those related to peroxisome proliferator-activated receptors(PPAR) and AMP-activated protein kinase(AMPK), with these findings subsequently verified experimentally. Conclusion These findings showed that YQRG improved CCl4-induced liver fibrosis through multiple mechanisms and pathways, offering critical insight into the YQRG-related therapeutic mechanism and promoting further research into its potential application.